Behaviour of axially discontinuous thin-walled frame structures when subjected to torsion / Osman Abdullah - Abdullah, Osman (1997)
The main objective of this project is to study the behaviour of an axially Discontinuous Thin-Walled Structures under torsional load. Material test will be carried out on samples taken from both the member to determine the complete uniaxial stress-strain characteristics of the materials from which the modulus of elasticity and uniaxial yield stress can be extracted. Strains perpendicular to the direction of the applied stress will also be recorded for calculating Poisson's ratio. A simple model was used to represent completely the behaviour of this thin walled structure with respect to bending and torsional. A simple model will be used to represent completely the behaviour of this thin walled structure with respect to bending and torsional.